Risk factors of aspiration in neurocritical care patients with enteral nutrition (神经重症肠内营养支持患者误吸危险因素分析) - WANG Dan (王丹); KUANG Hongmei (况红梅); LIU Weichen (刘韦辰) (中西医结合护理)
Objective To analyze the influencing factors of aspiration in neurocritical care patients with enteral nutrition, and to provide a reference for formulating strategies to prevent the incidence of aspiration. Methods From July 2020 to July 2021, 527 neurocritical care patients with enteral nutrition in a tertiary hospital in Jiangxi Province were selected, and they were divided into aspiration group and non-aspiration group according to whether aspiration occurred. The univariate and logistic regression analysis were used to analyze risk factors of aspiration. Results Totally 105 patients were included in the aspiration group and 422 patients in the non-aspiration group. The results of logistic regression showed that aspiration history (OR= 28. 122), sedative hypnotics (OR= 3. 188), catheterization depth (OR=0. 853) and Glasgow Scale score (OR= 0. 671) were the influencing factors of aspiration in neurocritical care patients with enteral nutrition. Conclusion The influencing factors of aspiration in neurocritical patients with enteral nutrition are various and complex, nurses should pay more attention to the risk factors, and taking protective measures in time to reduce the incidence of aspiration. (目的 调查神经重症患者肠内营养误吸的影响因素, 为制定防误吸策略和降低患者误吸发生率提供参考依据。方法 2020年7月—2021年7月, 选取江西省某三甲医院采用肠内营养支持的神经重症患者527例, 根据是否发生误吸分为误吸组和非误吸组, 应用单因素与Logistic回归分析神经重症患者肠内营养误吸的危险性因素。结果 共纳入患者527例中误吸组105例, 非误吸组422例。Logistic回归结果显示误吸史(OR＝28. 122)、镇静催眠药(OR＝3. 188)、置管深度(OR=0. 853)、格拉斯哥昏迷评分(OR＝0. 671)是神经重症患者肠内营养误吸的影响因素。结论 神经重症患者肠内营养误吸的影响因素多而复杂, 护理人员需加强对误吸高危因素的识别与防护, 及时采取防护措施, 降低误吸发生率。)